ARTIFICIAL INTELLIGENCE TOOLS IN MANAGING DIGITAL MARKETING COMMUNICATIONS OF SPORTS ORGANIZATIONS (Development Service Industry Management, 2025)
The growing role of digital technologies in the field of sports requires the implementation of artificial intelligence tools to increase the effectiveness of marketing communications and strengthen the competitive positions of sports organizations. The purpose of the study is to identify and systematize artificial intelligence tools suitable for managing marketing communications in sports organizations and to verify their effectiveness. The article examines the application of artificial intelligence tools in managing digital marketing communications of sports organizations. It is shown that against the background of growing competition between sports and the entertainment industry, it is the quality of digital communications, personalization and data work that are becoming critical for recruiting, image and attracting partners. Artificial intelligence tools are summarized and systematized by functional blocks: data collection and formation of analytical reports; content generation (texts, images, videos); advertising and targeting; communications and service, reputation monitoring. The article examines the impact of artificial intelligence tools on the effectiveness of managing marketing communications of sports organizations. Using the example of the Lviv Lions sports club, an experiment was conducted on the phased introduction of AI into key communication processes. At the first stage, an AI copywriter and image generator were implemented to create adapted content and unique visual materials. The second stage involved the use of intelligent algorithms in contextual advertising (Google Ads, Facebook, Instagram) with the use of automatic bidding strategies to optimize the budget and attract new athletes. The third stage included the development and implementation of an AI chatbot integrated into the website and messengers, which ensured the automation of answers to typical questions and the transfer of leads to the CRM system. The results of the experiment showed a significant increase in the efficiency of digital communications, an increase in the number of calls, cost optimization, and improved interaction with the target audience. The article emphasizes the prospects of using artificial intelligence as an innovative tool for the development of marketing communications in sports organizations.
Keywords: artificial intelligence; marketing communications; sports organizations; digital marketing; smart bidding; chatbot, generative; chatbot; generative AI